Gut, inflammation and osteoporosis: basic and clinical concepts. Issue 5 (11th April 2008) - Tilg, H; Moschen, A R; Kaser, A; Pines, A; Dotan, I
Abstract : Chronic inflammatory disorders such as inflammatory bowel diseases (IBD) affect bone metabolism and are frequently associated with the presence of osteoporosis. Bone loss is regulated by various mediators of the immune system such as the pro-inflammatory cytokines tumour necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), IL-6, or interferon-gamma. TNF-α, a master cytokine in human IBD, causes bone erosions in experimental models and these effects are exerted by osteoclasts. Other TNF-related cytokines such as receptor activator of nuclear factor kappa B (RANK), its ligand, RANKL, and osteoprotegerin are important mediators in inflammatory processes in the gut and are critically involved in the pathophysiology of bone loss. The awareness and early diagnosis of osteoporosis in states of chronic inflammation, together with applied therapies such as bisphosphonates, may be beneficial in inflammation-associated osteoporosis. Although several mechanisms may contribute to osteoporosis in patients with IBD and coeliac disease, inflammation as an important factor has so far been neglected. As key inflammatory mediators in IBD such as TNF-α are involved in the disease process both in gut and bone, we hypothesise that neutralisation of TNF-α could prove an efficient strategy in the treatment of inflammation-related osteoporosis in the future.